Liver-protectant and cardiovascular-protectant effects of Nigella sativa: a meta-analysis - Fathiyah Safithri; Diah Hermayanti; Isbandiyah; Probo Yudha Pratama Putra; Faiq Shabri Maulana; Aji Muthi'ah Nur Azizah (KeAi Communications Co., Ltd., 2023)
Objective: A significant amount of evidence has lately revealed that individuals with non-alcoholic fatty liver diseases (NAFLD) are at high risk of cardiovascular diseases, which is the primary cause of death in patients. This study is to evaluate liver- and cardiovascular-protectant effects of Nigella sativa (N. sativa). Methods: The meta-analysis was performed using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The literature review was conducted in June 2022 with papers retrieved from the PubMed, ScienceDirect, and Cochrane Library websites from January 2010 to December 2021. The Review Manager version 5.3 was applied for the statistical analysis of parameters like aspartate transaminase (AST) and alanine transaminase (ALT) levels, lipid profil, blood glucose level, weight, and body mass index (BMI). Results: The results showed that N. sativa could significantly decrease the AST (P = 0.009) and ALT (P < 0.05) levels in research subjects. Subjects in the N. sativa group had a significant higher cure rate of fatty liver than those in the placebo group (P = 0.0001). In addition, lipid profile, blood pressure, and fasting blood glucose of subjects all significantly reduced in the N. sativa group (P < 0.05). However, the comparison of body weight and BMI between the N. sativa group and placebo group did not show significant difference (P > 0.05). Conclusion: N. sativa did have certain liver-protectant and cardiovascular-protectant effects on patients with NAFLD or chronic liver diseases (CLD), despite the insignificant comparison of body weight and BMI between the N. sativa group and the placebo group.